VD_FINDINFO AP / 2009 / 94 vom 31. März 2009 - VD Tribunal cantonal (2009)
VOIES DE FAIT, LÉSION CORPORELLE SIMPLE, FIXATION DE LA PEINE, PEINE PÉCUNIAIRE | 123 ch. 1 CP, 126 CP, 34 CP, 47 CP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 411 let. j CPP, 415 CPP